Sex differences in the pituitary transforming growth factor-beta1 (TGF-beta1) system: studies in a model of resistant prolactinomas - Recouvreux, Maria Victoria (2013)
Dopamine and estradiol interact in the regulation of lactotroph cell proliferation and prolactin secretion. Ablation of the dopamine D2 receptor gene (Drd2 / ) in mice leads to a sexually dimorphic phenotype of hyperprolactinemia and pituitary hyperplasia, which is stronger in females. TGF- 1 is a known inhibitor of lactotroph proliferation. TGF- 1 is regulated by dopamine and estradiol, and it is usually down-regulated in prolactinoma experimental models. To understand the role of TGF- 1 in the gender-specific development of prolactinomas in Drd2 / mice, we compared the expression of different components of the pituitary TGF- 1 system, including active cytokine content, latent TGF- –binding protein isoforms, and possible local TGF- 1 activators, in males and females in this model. Furthermore, we evaluated the effects of dopamine and estradiol administration to elucidate their role in TGF- 1 system regulation. The expression of active TGF- 1, latent TGF- –binding protein isoforms, and several putative TGF- 1 activators evaluated was higher in male than in female mouse pituitary glands. However, Drd2 / female mice were more sensitive to the decrease in active TGF- 1 content, as reflected by the down-regulation of TGF- 1 target genes. Estrogen and dopamine caused differential regulation of several components of the TGF- 1 system. In particular, we found sex- and genotype- dependent regulation of active TGF- 1 content and a similar expression pattern for 2 of the putative TGF- 1 activators, thrombospondin-1 and kallikrein-1, suggesting that these proteins could mediate TGF- 1 activation elicited by dopamine and estradiol. Our results indicate that (1) the loss of dopaminergic tone affects the pituitary TGF- 1 system more strongly in females than in males, (2) males express higher levels of pituitary TGF- 1 system components including active cytokine, and (3) estradiol negatively controls most of the components of the system. Because TGF- 1 inhibits lactotroph proliferation, we propose that the higher levels of the TGF- 1 system in males could protect or delay the development of prolactinomas in Drd2 / male mice.